Cytotoxicity, biocompatibility and biomineralization of a new ready-for-use bioceramic repair material - Benetti, Francine [UNESP]; Queiroz, Índia Olinta de Azevedo [UNESP]; Cosme-Silva, Leopoldo [UNESP]; Conti, Leticia Citelli [UNESP]; de Oliveira, Sandra Helena Penha [UNESP]; Cintra, Luciano Tavares Angelo [UNESP] (FapUNIFESP (SciELO), 2019)
New mineral trioxide aggregate (MTA) formulations are constantly introduced in the market, usually in a powder-and-liquid form. Bioceramic (Bio-C) Repair is a ready-for-use material suggested as substitute for MTA, but its properties need to be studied. This study evaluated the cytotoxicity, biocompatibility and biomineralization of Bio-C Repair compared to MTA Repair High-Plasticity (MTA-HP) and white MTA-Angelus (MTA-Ang). L929 fibroblasts were exposed to material-extracted (undiluted, ½ and ¼ dilutions; 6, 24 and 48h). Polyethylene tubes with material or empty (control) were implanted in the subcutaneous tissue of rats. After 7 and 30 days (n=8), the specimens were removed for analysis (hematoxylin-eosin, von Kossa and polarized light). Cytotoxicity data were statistically analyzed by two-way ANOVA, and biocompatibility data by Kruskal-Wallis and Dunn tests (p<0.05). The cells exposed to the materials had greater viability at most of the periods compared with control (p<0.05). The undiluted and ½ dilutions of MTA-HP extract showed higher cytocompatibility than Bio-C Repair at 6 h and with the ¼ dilution at 24 h (p<0.05); the white MTA-Ang showed higher cytocompatibility than Bio-C Repair at most of periods (p<0.05). The undiluted white MTA-Ang extract had higher cytocompatibility at 6 and 24h than MTA-HP, and with ½ dilution at 24h (p<0.05). The materials’ cytocompatibility was similar at 48h for most dilutions (p>0.05). At 7 and 30 days, the groups had moderate and mild inflammation, respectively (p>0.05). All materials showed positive structures for von Kossa and polarized light. In conclusion, Bio-C Repair had similar cytocompatibility to MTA-based materials is biocompatible and induces biomineralization.
Keywords: Biocompatible materials; Cytotoxicity; Dental materials; Endodontics; Materials testing